Reporte de Caso: Absceso encapsulado ventral en el cuello de un mono aullador (Alouatta palliata) - Cárdenas, Dayanara (2025)
This report details a clinical case of a howler monkey with an encapsulated abscess in the ventral neck region affecting anatomical structures associated with its vocal ability. After receiving first aid at a wildlife rescue centre, the primate's clinical condition did not improve, prompting its transfer to the TUERI Wildlife Hospital of the Universidad San Francisco de Quito, Ecuador, where a clinical protocol was implemented with diagnosis through radiographs, laboratory analysis, and intensive treatment with surgical debridement, antibiotic therapy, and hospital care. The integrated application of these techniques effectively controlled the infection without compromising the primate's vital functions and vocal ability, ensuring its suitability for reintroduction to its natural habitat. This clinical case underscores the importance of rigorous and evidence-based clinical protocols for managing wildlife, emphasizing that appropriate initial intervention is essential to prevent complications and improve the patient's final prognosis.